Upaya Anak Berkebutuhan Khusus dalam Menghadapi Kurikulum Merdeka pada Pelajaran Matematika di Sekolah Umum - Karlenata, Hiis; Pujita Sari, Aldsy; Livia Susanti, Herizal (JPT : Jurnal Pendidikan Tematik, 2024)
The background of this research is to determine the efforts of children with special needs (ABK) to face the independent curriculum. The aim of this research is to determine the implementation of the independent curriculum, especially for children with special needs in public schools. The type of research is qualitative descriptive. The research population includes students and teachers who work in public schools. Data analysis was carried out using descriptive statistical analysis techniques. The results of the research show that children with special needs (ABK) in public schools do not experience difficulties in facing the independent curriculum, because teachers in these schools use visual learning media, props or projectors and pictures in the learning process. with assistance. Based on the results of data analysis, it can be concluded that the implementation of the Independent Curriculum for children with special needs in public schools is running smoothly according to the objectives.